FEATURES OF INTEGRAL INDICATORS OF THE NERVOUS SYSTEM IN THE DEVELOPMENT OF IMMOBILIZATION STRESS (E Global Congress, 2025)
Chronic immobilization stress negatively affects the central nervous system, causing structural and functional changes such as a decrease in gray matter volume, impaired neuroplasticity, disruptions in neurotransmitter systems (especially glutamate and GABA), and neuronal death. This leads to cognitive impairments, such as problems with memory and attention, and also increases the risk of developing neurodegenerative diseases. Studying the protective and pathogenetic aspects of immobilization stress remains an important area of ​​modern clinical physiology and pathophysiology. At the current stage of development of experimental and clinical medicine, stress and its accompanying comorbid pathologies are the foundation for a number of psychosomatic diseases. Such disorders are a widespread maladaptive phenomenon. For the full restoration of central nervous system functions after stress exposure, it was necessary to investigate the mechanisms of post-stress complications, to study the changes in brain function and metabolism in their interrelationship, thereby ensuring a comprehensive, integrated approach to understanding the pathogenesis of stress complications.